Role of non-executive directors in Malaysian public listed companies: background, literature, methodology and initial findings - Annuar, Hairul Azlan (2006)
Johnson, Daily and Ellstrand (1996) had noted that directors’ most significant duties consists of three overlapping roles of control, resource dependence and service, and that the board composition influences the effectiveness with which directors perform these roles. The paper presents the background, literature and methodology employed into a study investigating the role of non-executive directors (NEDs) in Malaysian public listed companies. Initial results derived from face-to-face interviews with 27 company directors reaffirm these propositions and provide evidence from the perspective of a developing nation of the expanding responsibilities of NEDs. The early findings bode well to the future of the corporate governance system of a country on the verge of recovering from the Asian crisis.